(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2017)
This article uses the comparative approach in analyzing four civil and political rights namely personal liberty, freedom of religion, gender equality and freedom of speech from international law and syariah perspectives. The analysis finds that the secular law of nations clearly differs from the religious law. Syariah contains restrictions and prohibitions (from committing sins) which are not recognized by the international human rights law. Nevertheless there are similarities between the two laws with regard to the aspect of personal liberty. Keywords: human rights, international law, syariah, personal liberty, freedom of religion, gender equality, freedom of expression